Jambi City Government's Strategy in Overcoming Parental Rejection of Diphtheria Tetanus Immunization at The Talang Bakung Health Center In Jambi City - Witri, Repelita; Putra, Marsudi Dedi; Kuntardjo, Carolina; Ropii, Imam (Dinasti Research, 2025)
This study aims to identify the factors that cause parents to refuse Diphtheria Tetanus immunization for children's health at the Talang Bakung Health Center, Jambi City, and analyze the legal strategies implemented by the Jambi City Regional Government in overcoming these rejections. The research method used is empirical legal research with a qualitative approach. Data was collected through interviews, observations, and documentation of related parties such as health workers, parents, and local government officials. Data analysis was carried out in a descriptive analytical manner by relating relevant field findings and legal theories. The results of the study showed that immunization refusal by parents was caused by several factors, including concerns about Post-Immunization Adverse Events (AEFIs), lack of understanding of vaccine benefits, the influence of misinformation on social media, and low trust in health workers. Social, cultural, and religious factors also contribute to strengthening resistance to immunization programs. The Jambi City Regional Government implements a persuasive and educational legal strategy by emphasizing increasing public health literacy through integrated socialization, the involvement of religious and community leaders, and the affirmation of legal policies based on Law Number 17 of 2023 concerning Health and Government Regulation Number 28 of 2024. In addition, the Regional Government strengthens legal protection for health workers and regulates the mechanism for handling AEFIs in a transparent manner to foster public trust. This legal strategy has proven effective in reducing immunization refusal rates and increasing community participation, although ongoing efforts are still needed to strengthen legal awareness and overall public health.